Estrategias de marketing para mejorar la calidad de atención en el Minimarket Max de la ciudad de Iquitos, 2023 - Ormeño Zubiate, Cesar Augusto (2023)
The title of the study is “Marketing strategies to improve the quality of service in Minimarket Max Iquitos 2023”. This study used a quantitative approach and a non-experimental design. To carry out a descriptive study. The Pearson chi-square value calculated by SPSS v 26 statistical program, with a significant degree and a bilateral significance value of 0.000; According to the decision rule: if the P value (asymptotic significance) is less than 0.05, reject the null hypothesis and accept the alternative hypothesis. The following hypothesis: There is a direct relationship between marketing strategies. This hypothesis asks: Is there a significant relationship between marketing strategies? of Minimarket Max, the quality of service based on the value obtained, to measure the reliability of the instrument, Cronbach's alpha was used and the results were 0.905, as it is close to 1, it has a high degree of reliability.